A HDPE halogen-free flame-retardant composite material for cables and preparation method thereof

By using composite materials with high-density polyethylene and specific additives in cable materials, the existing halogen-free flame retardant effects and interface problems are solved, and excellent flame retardant and mechanical properties are achieved.

CN119060437BActive Publication Date: 2025-02-28GAOLANDE (GUANGDONG) NEW MATERIALS TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411329603.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-02-28
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

When used in cable materials, the flame retardant effect is poor, and the excessive addition amount will lead to interface problems and damage mechanical and mechanical properties.

Method used

The HDPE halogen-free flame retardant composite material is prepared by using a composite material preparation method including high-density polyethylene, affinant, halogen-free flame retardant factor, inorganic modification factor, antioxidant, ultraviolet absorber and lubricant, and the HDPE halogen-free flame retardant composite material is prepared by mechanical stirring and mixing and twin screw extrusion process.

Benefits of technology

The composite material has achieved excellent flame retardant and other comprehensive properties, improved mechanical strength and flame retardant properties, reduced smoke generation, and avoided interface problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of composite materials, and discloses a HDPE halogen-free flame-retardant composite material for cables and a preparation method thereof. The composite material is prepared by mixing and melt extrusion processes using high-density polyethylene as a base material and using a halogen-free flame-retardant factor and an inorganic modifier as main additives. The halogen-free flame-retardant factor can be used as a self-contained expansion flame retardant, and can rapidly form an expansion carbon layer when the composite material burns to prevent continuous combustion, and can also absorb smoke generated by combustion to reduce smoke generated by combustion. The addition of the inorganic modifier can not only improve the mechanical strength of the composite material, but also uniformly disperse the illite to enable the illite to exert its own layered structure advantage to prevent the transfer of heat and oxygen during combustion, thereby further enhancing the flame retardant performance of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of composite materials, and in particular to a HDPE halogen-free flame-retardant composite material for cables and a preparation method thereof. Background Art

[0002] In modern society, cables are important infrastructure for power transmission and communication, and their safety and stability are directly related to the normal operation of various fields. As a highly crystalline, non-polar thermoplastic resin, high-density polyethylene (HDPE) not only has good physical and mechanical properties, but also has excellent electrical insulation properties. It is very suitable for the insulation layer and sheath of cables and has been widely used in cable manufacturing. However, with the increasingly stringent safety standards and environmental regulations, the flame retardant properties of cable materials have become the focus of attention. Traditional halogen flame retardants will produce toxic, corrosive gases and a large amount of smoke when burned, which not only threatens environmental safety, but may also cause serious harm to human health. Therefore, with the improvement of environmental awareness and the tightening of regulations, halogen-free flame retardants have gradually become the mainstream choice in the market. Halogen-free flame retardants do not produce toxic and harmful substances during combustion, have significant environmental advantages, and their flame retardant effect is also excellent, providing a strong guarantee for the safety performance of cable materials.

[0003] At present, halogen-free flame retardants are mainly divided into organophosphorus flame retardants and inorganic flame retardants. Organophosphorus flame retardants have good flame retardant effects, but small molecule phosphorus flame retardants will volatilize and migrate during use, making it difficult to achieve a sustained flame retardant modification effect. Although inorganic flame retardants will not migrate or volatilize, their flame retardant effects are relatively poor, and generally require a larger addition amount to achieve a considerable modification effect. However, an increase in the addition amount will cause serious interface problems between the inorganic flame retardant and high-density polyethylene, resulting in damage to the mechanical properties. Based on this, the present invention provides a HDPE halogen-free flame retardant composite material having excellent comprehensive properties such as flame retardancy, which can be directly used in cable manufacturing. Summary of the invention

[0004] In order to solve the problems mentioned in the background technology, the object of the present invention is to provide a HDPE halogen-free flame-retardant composite material for cables and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing a HDPE halogen-free flame-retardant composite material for cables, wherein the composite material is made of raw materials including the following parts by weight:

[0007]

[0008] The preparation method comprises the following steps:

[0009] The first step is to weigh each raw material according to the weight and set aside;

[0010] Step 2: Add high-density polyethylene, affinity agent, halogen-free flame retardant factor, inorganic modifier, antioxidant, ultraviolet absorber and lubricant into the mixing kettle, control the temperature to 80-100°C, the speed to 1000-2000r / min, and mechanically stir and mix for 30-40min to obtain a mixed material;

[0011] The third step is to feed the mixed material into a twin-screw extruder and obtain a composite material through a melt extrusion process.

[0012] As a further embodiment of the present invention, the preparation method of the affinity agent is as follows:

[0013] Natural rubber, isocyanoethyl methacrylate and initiator benzoyl peroxide are mixed and placed in a torque rheometer. The temperature is set to 170-180°C and the speed is set to 50-60rpm. After melt grafting for 5-10 minutes, the material is discharged and subjected to a post-treatment process to obtain an affinity agent.

[0014] As a further embodiment of the present invention, the method for preparing the halogen-free flame retardant factor comprises the following steps:

[0015] Step 1: add spirocyclic phosphoryl dichloride and tetrahydrofuran to a reactor filled with nitrogen, start stirring, and after a uniform solution is formed, add 3-(1H-imidazole-1-yl)propane-1,2-diol to the reactor, start heating, control the temperature to 60-65° C., keep warm for 6-9 hours, cool down and discharge the material to obtain a nitrogen-phosphorus cross-linked intermediate material;

[0016] Step 2: Disperse the loofah in 60% ethanol by volume, then add nitrogen-phosphorus crosslinking agent and acidifying agent, gradually increase the temperature to 60-65°C, keep stirring for 8-12 hours, pour it into a mold, let it stand to form a gel, then place it in a freeze dryer, and freeze-thaw cycles 2-4 times at a temperature of -50°C to obtain a halogen-free flame retardant factor.

[0017] As a further embodiment of the present invention, in step 1, the molar ratio of the spirocyclic phosphoryl dichloride to 3-(1H-imidazole-1-yl)propane-1,2-diol is 2:1.

[0018] As a further embodiment of the present invention, in step 2, the acidifying agent is triethylamine or pyridine.

[0019] In the above technical scheme, spirocyclic phosphoryl chloride and 3-(1H-imidazole-1-yl)propane-1,2-diol are first used as reaction monomers, and by controlling the dosage of each other, a nitrogen-phosphorus cross-linked intermediate material containing two equivalents of phosphoryl chloride groups in the structure is obtained, and then it is used as a cross-linking agent to cross-link the loofah sponge, and then the formed cross-linked product is freeze-dried through a freeze-drying process, so that an aerogel-type material with loofah sponge as the skeleton and a large amount of nitrogen-phosphorus flame retardant elements in the structure, that is, a halogen-free flame retardant factor, can be obtained.

[0020] As a further embodiment of the present invention, the preparation method of the inorganic modification factor is as follows:

[0021] The illite is ultrasonically dispersed in toluene solvent, and then polyglutamic acid and a phase transfer catalyst are added to the formed uniform dispersion. After the addition, the temperature is slowly raised to 90-100°C, and stirring is continued at this temperature for 8-12 hours. The heating is stopped, the temperature is lowered and the material is discharged. The solid material is collected by centrifugation, and the inorganic modification factor is obtained after washing and vacuum drying.

[0022] As a further embodiment of the present invention, the number average molecular weight of the polyglutamic acid is 10,000.

[0023] As a further embodiment of the present invention, the phase transfer catalyst is p-toluenesulfonic acid or trifluoromethanesulfonic acid.

[0024] In the above technical scheme, under the action of a phase transfer catalyst, the hydroxyl groups on the surface of illite can undergo esterification condensation with the active substituted carboxyl groups in the polyglutamic acid structure, thereby modifying the macromolecular substance polyglutamic acid on the surface of illite to obtain an inorganic modification factor.

[0025] As a further embodiment of the present invention, the antioxidant is antioxidant 168 or antioxidant 1010; the ultraviolet absorber is ultraviolet absorber UV-234 or ultraviolet absorber UV-120; and the lubricant is polyethylene wax or calcium stearate.

[0026] A HDPE halogen-free flame-retardant composite material for cables is prepared by adopting the preparation method.

[0027] Beneficial effects of the present invention:

[0028] (1) The present invention first prepares an aerogel-type material with loofah as the skeleton and containing a large amount of nitrogen and phosphorus flame retardants in the structure as a halogen-free flame retardant factor. The loofah in the structure can be used as a carbon source, and the nitrogen and phosphorus flame retardants can provide an acid source and a gas source. Therefore, the halogen-free flame retardant factor can be used as a self-contained expandable flame retardant, which can quickly form an expandable carbon layer when the composite material burns to prevent the continued combustion. In addition, the special pore structure of the aerogel can also absorb the smoke generated by the combustion and reduce the smoke generated by the combustion.

[0029] (2) The present invention prepares illite with surface modified with polyglutamic acid macromolecule as an inorganic modifying factor. Polyglutamic acid can interact with the isocyanate substituent in the affinity agent structure during high-temperature melting, thereby greatly improving the dispersion effect of illite in high-density polyethylene, thereby effectively exerting its own reinforcing effect, which can not only improve the mechanical strength of the composite material, but also enable the illite to exert its own layered structure advantage through uniform dispersion, thereby preventing the transfer of heat and oxygen during combustion, thereby further enhancing the flame retardant properties of the composite material.

[0030] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0032] Figure 1 This is the infrared analysis test chart of nitrogen-phosphorus cross-linked intermediate material;

[0033] Figure 2 This is a scanning electron microscope image of the halogen-free flame retardant factor. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Preparation Example 1

[0036] Preparation of affinity agent:

[0037] 5g of natural rubber, 1.2g of isocyanoethyl methacrylate and 0.1g of initiator benzoyl peroxide were mixed and placed in a torque rheometer. The temperature was set to 180°C and the speed was set to 50rpm. After melt grafting for 10 minutes, the material was discharged and subjected to post-treatment to obtain an affinity agent.

[0038] Preparation Example 2

[0039] Preparation of halogen-free flame retardant factors:

[0040] Step 1: add 0.2 g of spirocyclic phosphoryl dichloride and tetrahydrofuran to a reactor filled with nitrogen, start stirring, and after a uniform solution is formed, add 0.05 g of 3-(1H-imidazole-1-yl)propane-1,2-diol to the reactor, start heating, control the temperature to 65°C, keep warm for 8 hours, cool down and discharge, and obtain a nitrogen-phosphorus cross-linked intermediate material;

[0041] Figure 1 This is the infrared analysis test diagram of the nitrogen-phosphorus cross-linked intermediate material. It can be observed from the figure that there is no obvious hydroxyl characteristic absorption peak, 1251cm -1 The P=O characteristic absorption peak appears at 500-600cm -1 The P-Cl characteristic absorption peak appeared at .

[0042] Step 2: Disperse 1.5 g of luffa lao in 60% ethanol by volume, then add 0.8 g of nitrogen-phosphorus crosslinking agent and 0.5 g of triethylamine, gradually increase the temperature to 65°C, keep stirring for 9 hours, pour it into a mold, let it stand to form a gel, then place it in a freeze dryer, and freeze-thaw cycles three times at a temperature of -50°C to obtain a halogen-free flame retardant factor.

[0043] Figure 2 This is a scanning electron microscope image of the halogen-free flame retardant factor. It can be seen from the image that it has a rich pore structure, and the pore structure is uniform. It has aerogel properties and can absorb a large amount of smoke generated by combustion.

[0044] Preparation Example 3

[0045] Preparation of inorganic modifiers:

[0046] 2.6 g of illite was ultrasonically dispersed in toluene solvent, and then 8.5 g of polyglutamic acid with a number average molecular weight of 10,000 and 0.5 g of p-toluenesulfonic acid were added to the formed uniform dispersion. After the addition, the temperature was slowly raised to 95°C, and stirring was continued at this temperature for 9 hours. The heating was stopped, the temperature was lowered and the material was discharged. The solid material was collected by centrifugation, and the inorganic modification factor was obtained after washing and vacuum drying.

[0047] The percentage of organic elements in the inorganic modified factor was analyzed using an organic element analyzer. 0.3 g of the inorganic modified factor was taken as a test sample. After testing, the percentage of carbon element was 16.71% and the percentage of nitrogen element was 3.89%. Obviously, these organic elements were provided by polyglutamic acid.

[0048] Example 1

[0049] A HDPE halogen-free flame-retardant composite material for cables is made of raw materials including the following parts by weight:

[0050]

[0051] The preparation method of the composite material comprises the following steps:

[0052] The first step is to weigh each raw material according to the weight and set aside;

[0053] Step 2: Add high-density polyethylene, affinity agent, halogen-free flame retardant factor, inorganic modifier, antioxidant 168, ultraviolet absorber UV-234 and polyethylene wax into a mixing kettle, control the temperature to 80°C, the speed to 1000r / min, and mechanically stir and mix for 40 minutes to obtain a mixed material;

[0054] The third step is to feed the mixed material into a twin-screw extruder, control the screw speed to 100r / min, and the extrusion temperature to 240°C, and obtain a composite material through a melt extrusion process.

[0055] The affinity agent in this embodiment is prepared by the preparation method of Preparation Example 1; the halogen-free flame retardant factor is prepared by the preparation method of Preparation Example 2; the inorganic modification factor is prepared by the preparation method of Preparation Example 3, and the same applies below.

[0056] Example 2

[0057] A HDPE halogen-free flame-retardant composite material for cables is made of raw materials including the following parts by weight:

[0058]

[0059]

[0060] The preparation method of the composite material comprises the following steps:

[0061] The first step is to weigh each raw material according to the weight and set aside;

[0062] Step 2: Add high-density polyethylene, affinity agent, halogen-free flame retardant factor, inorganic modifier, antioxidant 1010, ultraviolet absorber UV-120 and calcium stearate into the mixing kettle, control the temperature to 100°C, the speed to 1500r / min, and mechanically stir and mix for 40 minutes to obtain a mixed material;

[0063] The third step is to feed the mixed material into a twin-screw extruder, control the screw speed to 100r / min, and the extrusion temperature to 240°C, and obtain a composite material through a melt extrusion process.

[0064] Example 3

[0065] A HDPE halogen-free flame-retardant composite material for cables is made of raw materials including the following parts by weight:

[0066]

[0067]

[0068] The preparation method of the composite material comprises the following steps:

[0069] The first step is to weigh each raw material according to the weight and set aside;

[0070] Step 2: Add high-density polyethylene, affinity agent, halogen-free flame retardant factor, inorganic modifier, antioxidant 1010, ultraviolet absorber UV-120 and calcium stearate into the mixing kettle, control the temperature to 100°C, the speed to 2000r / min, and mechanically stir and mix for 40 minutes to obtain a mixed material;

[0071] The third step is to feed the mixed material into a twin-screw extruder, control the screw speed to 100r / min, and the extrusion temperature to 240°C, and obtain a composite material through a melt extrusion process.

[0072] Comparative Example 1

[0073] A HDPE halogen-free flame-retardant composite material for cables, which is different from Example 2 in that the halogen-free flame-retardant factor is removed and the rest remains unchanged.

[0074] Comparative Example 2

[0075] A HDPE halogen-free flame-retardant composite material for cables, which is different from Example 2 in that the inorganic modification factor is replaced by illite, and the rest remains unchanged.

[0076] Comparative Example 3

[0077] A HDPE halogen-free flame-retardant composite material for cables, which is different from Example 2 in that the inorganic modification factor is removed and the rest remains unchanged.

[0078] Test Case

[0079] The composite materials in the embodiments and comparative examples were made into test samples, and various performance tests were performed. The results are shown in Table 1:

[0080] Table 1 - Performance test results

[0081] Tensile strength / MPa Limiting oxygen index / % <![CDATA[Total smoke generation amount / m 2 / m 2 > Example 1 92.4 32.1 134.0 Example 2 92.7 32.6 132.9 Example 3 92.6 32.2 133.3 Comparative Example 1 92.0 21.5 169.1 Comparative Example 2 85.3 31.9 134.8 Comparative Example 3 70.9 31.0 137.4

[0082] Note: The tensile strength is tested according to the standard GB / T 1040-2008;

[0083] The limiting oxygen index is tested according to the standard GB / T 2406-2008;

[0084] The total smoke production test method is as follows: take a sample with a size of 10cm×10cm×5mm, wrap it with aluminum foil, and then place it in a cone calorimeter at a heat flux radiation intensity of 25Kw / m 2 The test was conducted under the conditions that the exhaust pipe flow rate was set to 24L / s and the distance between the sample and the radiation cone was 10mm.

[0085] From the analysis and test results, it can be seen that the composite material made with halogen-free flame retardant factor and inorganic modification factor as additives has excellent flame retardant properties and high mechanical strength. After removing the halogen-free flame retardant factor, the flame retardant properties dropped significantly, and the total smoke generation increased significantly. After replacing the inorganic modification factor with illite, due to the problem of interface incompatibility, the illite could not play an efficient role, resulting in a decrease in the mechanical strength of the material. After completely removing the inorganic modification factor, not only the mechanical strength decreased, but also the flame retardant properties decreased slightly. It can be concluded that the addition of illite has a positive effect on improving the flame retardant properties of composite materials.

[0086] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. A method for preparing a HDPE halogen-free flame-retardant composite material for cables, characterized in that: The composite material is made of the following raw materials in parts by weight: The preparation method comprises the following steps: The first step is to weigh each raw material according to the weight and set aside; Step 2: Add high-density polyethylene, affinity agent, halogen-free flame retardant factor, inorganic modifier, antioxidant, ultraviolet absorber and lubricant into the mixing kettle, control the temperature to 80-100°C, the speed to 1000-2000r / min, and mechanically stir and mix for 30-40min to obtain a mixed material; The third step is to feed the mixed material into a twin-screw extruder and obtain a composite material through a melt extrusion process; The preparation method of the affinity agent is as follows: Mix natural rubber, isocyanoethyl methacrylate and initiator benzoyl peroxide, place in a torque rheometer, set the temperature to 170-180°C, set the speed to 50-60rpm, perform melt grafting for 5-10 minutes, discharge the material, and obtain the affinity agent through post-treatment process; The preparation method of the halogen-free flame retardant factor comprises the following steps: Step 1: add spirocyclic phosphoryl dichloride and tetrahydrofuran to a reactor filled with nitrogen, start stirring, and after a uniform solution is formed, add 3-(1H-imidazole-1-yl)propane-1,2-diol to the reactor, start heating, control the temperature to 60-65° C., keep warm for 6-9 hours, cool down and discharge the material to obtain a nitrogen-phosphorus cross-linked intermediate material; Step 2: Disperse the loofah in 60% ethanol by volume, then add the nitrogen-phosphorus cross-linking intermediate and the acidifying agent, gradually raise the temperature to 60-65°C, keep stirring for 8-12 hours, pour it into a mold, let it stand to form a gel, and then place it in a freeze dryer, and freeze-thaw 2-4 times in a temperature environment of -50°C to obtain a halogen-free flame retardant factor; The preparation method of the inorganic modification factor is as follows: The illite is ultrasonically dispersed in toluene solvent, and then polyglutamic acid and a phase transfer catalyst are added to the formed uniform dispersion. After the addition, the temperature is slowly raised to 90-100°C, and stirring is continued at this temperature for 8-12 hours. The heating is stopped, the temperature is lowered and the material is discharged. The solid material is collected by centrifugation, and the inorganic modification factor is obtained after washing and vacuum drying.

2. The method for preparing a HDPE halogen-free flame-retardant composite material for cables according to claim 1, characterized in that: In step 1, the molar ratio of the spirocyclic phosphoryl dichloride to 3-(1H-imidazole-1-yl)propane-1,2-diol is 2:

1.

3. The method for preparing a HDPE halogen-free flame-retardant composite material for cables according to claim 1, characterized in that: In step 2, the acidifying agent is triethylamine or pyridine.

4. The method for preparing a HDPE halogen-free flame-retardant composite material for cables according to claim 1, characterized in that: The number average molecular weight of the polyglutamic acid is 10,000.

5. The method for preparing a HDPE halogen-free flame-retardant composite material for cables according to claim 1, characterized in that: The phase transfer catalyst is p-toluenesulfonic acid or trifluoromethanesulfonic acid.

6. The method for preparing a HDPE halogen-free flame-retardant composite material for cables according to claim 1, characterized in that: The antioxidant is antioxidant 168 or antioxidant 1010; the ultraviolet absorber is ultraviolet absorber UV-234 or ultraviolet absorber UV-120; and the lubricant is polyethylene wax or calcium stearate.

7. A HDPE halogen-free flame-retardant composite material for cables, characterized in that: The method is prepared according to claim 1.

Citation Information

Patent Citations

  • Low-smoke halogen-free cable and preparation method thereof

    CN115594907A